2018
DOI: 10.2147/tcrm.s178297
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a pharmacist-led adverse drug event management model for pharmacovigilance in an academic medical center hospital in China

Abstract: BackgroundSpontaneous reporting of adverse drug events (ADEs) has long been the cornerstone of pharmacovigilance. Medical institutions in China have been a major source of ADE case reports, but the proportion of reports from tertiary hospitals is low due to the serious underreporting of case reports. The same problem existed in the Second Affiliated Hospital of Zhejiang University School of Medicine (SAHZU).ObjectiveIn order to increase the number of ADE reports and promote hospital pharmacovigilance, SAHZU’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
(14 reference statements)
1
12
0
1
Order By: Relevance
“…Twenty‐six studies examined the impact of IMS by different methods in both developed and developing countries. The positive effect of IMS on ADR reporting varied widely, from 1.02 to 83.9‐fold . As shown in Table , the range of effect of IMS was nearly similar to the effect of educational interventions and computerized registration.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Twenty‐six studies examined the impact of IMS by different methods in both developed and developing countries. The positive effect of IMS on ADR reporting varied widely, from 1.02 to 83.9‐fold . As shown in Table , the range of effect of IMS was nearly similar to the effect of educational interventions and computerized registration.…”
Section: Resultsmentioning
confidence: 77%
“…Out of the 90 studies, 16 were from France; eight from Italy; seven from the United States and Spain; six from the United Kingdom and Portugal; four from Iran and India; three from China, Sweden, and Mexico; two from Brazil, Denmark, Israel, Korea, the Netherlands, Switzerland, and the United Arab Emirates; and one each from Chile, Germany, Morocco, Nigeria, Saudi Arabia, South Africa, and Thailand. The interventions were designed as before‐after in 50 of the studies, non‐comparative in 17 studies, randomized controlled trial (RCT) and cluster RCT in nine studies, and other in 14 studies. In addition, most of the studies had been developed on HCPs, particularly physicians.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to a study in France that found that only 12.7% of ADR reports from GPs were "well-documented." 19) However, it seems likely that the quality of ADR reports could be improved in China.…”
Section: Discussionmentioning
confidence: 99%